Service Orientation and Career Preparation Among Undergraduate Students - Novenda Sheila Divadhani; Heri Prabowo; Farah Chalida Hanoum (Jurnal Riset Akuntansi, 2026)
This study examines the interrelationships between service orientation, career planning behaviours, training expectations, and self-efficacy among undergraduate students preparing for service industry careers. Methods: Using a quantitative correlational design, data were collected from 202 undergraduate students via a structured questionnaire. Pearson correlation analysis was conducted to examine relationships among key variables. Findings: Service orientation demonstrated significant positive correlations with all other constructs (r = .205 to .275, p < .01), positioning it as a central element in career preparation. The strongest correlation was observed between career research and clear career goals (r = .407, p < .01), while clear career goals and training relevance showed no significant relationship (r = .119, p > .05). Implications: The findings suggest that service orientation should be integrated into career development programs and that holistic approaches addressing multiple constructs simultaneously may be particularly effective. Originality: This study extends Social Cognitive Career Theory by incorporating service orientation as a key variable and applies service-dominant logic to career preparation processes.